Driven by Clients: A Variant of Clientelism and Its Consequences for Democracy - Martín Ordóñez (Latin American Research Review)
Clientelism is traditionally viewed as a mechanism through which patrons exert control over clients. Drawing on qualitative data from three municipalities in Santiago, Chile, and building on literature that emphasizes client agency, this article explores a variant of clientelism in which clients initiate and enforce clientelistic relationships. The findings suggest that these two forms of clientelism can differently impact a crucial aspect of democracy: horizontal accountability. Client-driven clientelism compels patrons to seek resources for distribution, rendering them susceptible to influence by those who can grant them access to these resources. When patrons are tasked with accountability roles and the resource providers are subject to their oversight (as in the relationship between municipal councilors and mayors), the providers can deter these accountability functions. In contrast, patrons with independent access to resources can better preserve their autonomy.